Hipocoagulation in Patients with Atrial Fibrillation and Admitted for Hemorrhagic Stroke - Santos, Maria Beatriz (2023)
Introduction: The stroke prevention strategy in patients with intracerebral hemorrhage (ICH) and atrial fibrillation (AF) is a clinical dilemma. The aim of this study was to evaluate themanagement of anticoagulation therapy in patients with AFand admitted with ICH. Methods: We performed a descriptive analysis of patientsadmitted for ICH from 2009 to 2021. Data collection was carried out by consulting the processes and analyzing demographic, clinical and imaging data, and prior and post-discharge therapy. A comparative analysis of outcomes of anticoagulant therapy was performed between direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs). Results: A total of 28 patients (22 male patients; median age 75 years) were included in the study, of which 19 were previously on anticoagulation therapy. Only eight (re)startedanticoagulation after discharge. There were 19 deaths, of which 17 were in the group without post-discharge anticoagulation; of those, five occurred in the first month after ICH. Discussion: There was strong concordance between BFFA and culture for detection of bacteria. In fact, most bacteria (76/106 [72%]) detected by BFFA were also identified in culture. In other hand, it is relevant that only one negative BFPP had an isolated agent in the cultural exam. Conclusion: Most patients did not (re)initiate anticoagulationafter ICH, despite being a high-risk group for new cerebrovascular events, which makes the discussion on this topic evenmore relevant. There was a change in the prescription pattern from VKAs to DOACs, comparing the two periods analyzed.